Normal standards of fetal behavior assessed by four-dimensional sonography - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2006)
Objective. In this prospective randomized study, fetal behavior was investigated in order to determine the standard parameters of fetal movements and facial expressions in all three trimesters of normal pregnancy. Methods. Sixty-three pregnant women with singleton pregnancies in all trimesters were included in the investigation. Four-dimensional (4D) ultrasound was performed for each patient over a 30-minute period. Variables of maternal and fetal characteristics including gestational age, eight fetal movement patterns in the first trimester, and sixteen parameters of fetal movement and fetal facial expression patterns in the second and third trimesters were recorded for the construction of fetal neurological charts. Results. In the first trimester, a tendency towards an increased frequency of fetal movement patterns with increasing gestational age was noticed. Only the startle movement pattern seemed to occur stagnantly during the first trimester (p > 0.05). At the beginning of the second trimester, the frequency of fetal movement patterns tended to increase. During the second and third trimester, multiple regression and polynomial regression revealed statistically significant changes in tongue expulsion (p < 0.05), smiling (p < 0.05), grimacing (p < 0.05), swallowing (p < 0.05), eye blinking (p < 0.01), head movements, and all hand to body contact movements (p < 0.01), except for head anteflexion (p > 0.05). There were no statistically significant changes during the second and third trimesters in mouthing, yawning, and sucking (p > 0.05). At the middle of the third trimester, the fetuses displayed decreasing or stagnant incidence of fetal facial expressions except for eye blinking, which showed increased frequency with increasing gestational age. A statistically significant correlation was found between all head movements and hand to body contact patterns during the second and third trimesters except for head anteflexion (r = -0.231; p > 0.05). Conclusions. The full range of quantitative fetal facial expressions and fetal movement patterns can be assessed successfully by 4D sonography. It is important to be able to assess normal fetal behavior throughout gestation to identify abnormal behavior before birth.
Keywords: fetal behavior; fetal movements; four-dimensional ultrasound; normal behavioral standards in pregnancy; NORMAL-PREGNANCY; MOVEMENTS; FETUS; ULTRASOUND; EMERGENCE; PRETERM; LIFE